CIVIC EDUCATION BERBASIS KEARIFAN LOKAL - Ngimadudin Ngimadudin (Edification Journal : Pendidikan Agama Islam, 2019)
Caring for the nationality is managing this unitary Republic of Indonesia to become "gemah ripah loh jinawi toto tentrem kertoraharjo". In Indonesian terminology is a sentence which is an expression to describe the condition of the Indonesian motherland. Gemah ripah means jinawi (abundant natural wealth) while toto tentrem karto raharjo (peaceful state). Or in the Arabic sense to be baldattun toyyibatun wa robbun ghoffur. This expression is not and mertajadi when the management of the State deviates from the importance of nation and state prosperity. Local (local wisdom) wisdom becomes the essence that must be able to be maintained in the midst of the storm of global ideology which ignores human values. When the young generation begins to forget the historical and cultural roots from which it originated, then he will get lost in the search for his true identity.